Menyingkap Dampak Positivisme Terhadap Esensi Penciptaan Manusia - Achsin, M. (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2006)
The paper aims at illuminating a history on the development of positivism and understanding its strength, weakness, inferiority, and superficiality. The paper also elaborates why and what secrete does remain behind such that it determines its accepted position throughout the philosophic and scientific worlds for hundreds years until now. The paper considers the view developed by The Father of Modem Philosophy the rationalist Rene Descartes (known as Renate Cartesius), the empiricist David Hume, following with rationalist- empiric Immanuel Kant throughout August Comte thought to ascertain the glory of positivist tradition. These only represent the birth and the development of â€œexistedâ€ positivism in the jungle of paradigm, philosophy and science. The final statement will be the explanation of human effort to escape from positivism fetter and to become â€œthe intact humanâ€ and â€œthe existing oneâ€ in the self and in the environment. Keywords: positivism, human creation